Interaksi Agama dan Politik dalam Konteks Tafsir Kontemporer - Saputra, Dimas Alan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research highlights a very relevant issue, namely the context of the interaction between religion and politics in contemporary interpretation The discussion on the role of religion in politics never ends. Islam is considered the last and perfect religion because of its universal scope, covering contemporary issues such as politics and governance. Islamic historians have produced a great deal of literature on this topic, with almost all schools of Islam discussing it, especially in the context of revivalists and modernists in the modern era. By using the Library research type research method, while the approach used by the author is analytical-constructive-critical, the interpretation method used is a thematic interpretation approach to analyze verses relevant to the research theme, with an emphasis on Contemporary Interpretation. To find out the interaction of religion and politics in the context of contemporary interpretation. This research aims to explore the concept of politics in the perspective of Contemporary Interpretation and its relevance to the relationship between religion and the state. The findings of the study show that the concept of politics in Contemporary Interpretation identifies the existence of a dualism between rational effort that can be understood through human ability, and a superrational dimension that is unreachable by logic. This concept is relevant to the pragmatic relationship between religion and the state, where the state is considered to be in line with religious values if its leader practices worship rituals with obedience.